Both Muslim and European diasporic and migrant identities of Bosniaks - Šuško, ǅevada (Muslim minorities, 2019)
"The edited volume Both Muslim and European: Diasporic and Migrant Identities of Bosniaks scrutinizes some of the new aspects of the Bosniak history and identity and connects them with the experience of migration and diaspora formation. Adopting an interdisciplinary approach, to volume tackles a variety of important questions and issues such as: the impact of migration waves on the Bosniak identity; dealing with the experience of war, genocide and forced displacement; the dual cultural code of being "in-between the two worlds"; the role of religion, language and culture in everyday life; looking at translocal and transnational networks and practices. In addition to discussing the contemporary issues in Bosnia and Herzegovina, several chapters deal with the Bosnian migrant realities in countries such as Germany, Switzerland, Slovenia, Australia, Turkey and the United States of America."